Postpartum Hemorrhagic Stroke Due to Cerebral Arterio-Venous Malformation Rupture: A Case Report - Parveen, Sazia; Ahmad, Afsari; Ahmed, Polly; Ahmed, Syed Sayed (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Stroke risk is 3 times higher in pregnancy and postpartum time than normal and carries high mortality and morbidity. Both ischemic and hemorrhagic strokes can occur during pregnancy and postpartum time up to 12 weeks after delivery. During this time hemodynamic changes occur in circulatory and vascular system which increases risk of coagulopathy. This may cause stroke. Hemorrhagic strokes are less common type but have a higher morbidity & mortality. We report a case of 38 years old patient with no known co-morbidities, experienced hemorrhagic stroke in her postpartum time because of cerebral arterio-venous malformation (AVM) rupture following elective cesarean section. She was treated surgically by decompressive craniotomy and removal of hematoma and excision of AVM. The case highlights the need for identification of signs and symptoms of stroke as early as possible and need for a multidisciplinary approach when there is a diagnostic dilemma, particularly in the postpartum period. J Bangladesh Coll Phys Surg 2025; 43: 81-84